Open Surgical Repair of Abdominal Aortic Aneurysm Coexisting with Horseshoe Kidney - Han, Ahram (Vasc Specialist Int, 2015)
Horseshoe kidney (HSK) is the most common congenital abnormality of the urologic system encountered during abdominal aortic aneurysm (AAA) surgery. Here, the authors report a case of AAA coexisting with HSK that was successfully treated by open surgery. Two accessory renal arteries of 2.5 mm and 3.1 mm were reimplanted. One of the implanted arteries later occluded and infarct of the isthmus developed, but there was no impairment of renal function. The authors discuss the complexity of the surgical treatment of AAA coexisting with HSK, and place focus on which accessory renal arteries should be reconstructed.